Different effects of various protein and ammonium chloride products - Craig, Ashley M.; Sorensen, Rachel J.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Many livestock producers want products that gets them the greatest gain for the lowest price. Our objective was to measure effects of varying protein sources and ammonium chloride incorporation on feedlot goat growth and carcass traits. A hypothesis that we expected was that SoyPlus as a protein source would result in better carcass traits than dried distiller grains (DDGS). In order to test this hypothesis, we had allotted 75 whethers and dolings into indoor pens at the Kansas State University Sheep and Meat Goat Center. Goats were randomly put into 25 pens (5pens/treatment; 3 goats/pen) based on their body weight when they had been received to be on a 42d finishing study. Five treatments were calculated to have the same caloric count were: 1) 18.7% soybean meal (SMB) with 0.75% ammonium chloride (AmCl), 2) 34.4% DDGS with 0.75% AmCl, 3) 22% SoyPlus with 0.75% AmCl, 4) 17.2% SMB with 4.83% SoyChlor, and 5) 20% Soyplus with 4.83% SoyChlor. Goats stayed on a self-feeder ad libitum, along with giving them fresh water twice a day and clean-living quarters. Goats were weighed weekly to get 14 measurements, however only looking at two, the first and the last weights of the trial. Since we measured weekly we looked at the beginning and total growth through the end of the trial and calculated BW, ADG, ADFI, and G:F. The beginning BW was similar at the start (P=0.57). By adding different protein/ ammonium chloride sources at 42d the BW (P=0.284), ADFI (P=0.140), ADG (P=0.099), and G:F (P=0.431) seemed to have no huge impact on carcass growth. These results fail our hypothesis that SoyPlus doesn’t produce better carcass traits. Although when looking at current prices treatment 2 has the lowest cost with no significant carcass difference than the other four treatments, showing the best cost benefit.
Keywords: Fall 2018